Dakota Gold®-brand dried distiller’s grains with solubles: effects on finishing performance and carcass characteristics - Gordon, C.M.; Gosch, J.; Sindt, J.J.; Montgomery, Sean P.; Pike, J.N.; Kessen, T.J.; Sulpizio, M.J.; Spire, M.F.; Higgins, James J.; Drouillard, James S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A 153-day trial was conducted using 345 heifers to determine optimal level of Dakota Gold dried distiller’s grains with solubles (DDGS) in finishing diets based on steam-flaked corn. Diets contained six levels of DDGS: 0%, 15%, 30%, 45%, 60%, and 75%. DDGS affected average daily gain, final weight and hot carcass weight, all of which increased with 15% DDGS and then decreased as additional DDGS was added. Growth performance of heifers fed 30% DDGS was similar to those fed no DDGS. In general, heifers were overfinished, with 61% being Yield Grade 3 or greater and 83% grading Choice or Prime. Backfat tended to decrease with addition of DDGS, and kidney, pelvic, and heart fat and marbling scores tended to be greatest for intermediate levels of DDGS. Percentage of carcasses grading Choice or Prime tended to be lower for heifers fed 60 or 75% DDGS.
Keywords: Beef; Dried distiller’s grains with solubles; Finishing cattle; Performance